Champa Grade 6 - "Ehsaan, Fouzi"; Fozia ehsaan farooqi (Lahore Oxford university press, 2024)
Each book is divided into three terms and each term has a significant number of lessons including prose and poem with SLOs and keywords used in the lesson are ...